Culture-Negative Septic Shock Compared With Culture-Positive Septic Shock: A Retrospective Cohort Study - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2018)
Objectives: To determine the clinical characteristics and outcomes of culture-negative septic shock in comparison with culture-positive septic shock. Design: Retrospective nested cohort study. Setting: ICUs of 28 academic and community hospitals in three countries between 1997 and 2010. Subjects: Patients with culture-negative septic shock and culture-positive septic shock derived from a trinational (n = 8,670) database of patients with septic shock. Interventions: None. Measurements and Main Results: Patients with culture-negative septic shock (n = 2,651; 30.6%) and culture-positive septic shock (n = 6,019; 69.4%) were identified. Culture-negative septic shock compared with culture-positive septic shock patients experienced similar ICU survival (58.3% vs 59.5%; p = 0.276) and overall hospital survival (47.3% vs 47.1%; p = 0.976). Severity of illness was similar between culture-negative septic shock and culture-positive septic shock groups ([mean and SD Acute Physiology and Chronic Health Evaluation II, 25.7 +/- 8.3 vs 25.7 +/- 8.1]; p = 0.723) as were serum lactate levels (3.0 [interquartile range, 1.7-6.1] vs 3.2 mmol/L [interquartile range, 1.8-5.9 mmol/L]; p = 0.366). As delays in the administration of appropriate antimicrobial therapy after the onset of hypotension increased, patients in both groups experienced congruent increases in overall hospital mortality: culture-negative septic shock (odds ratio, 1.56; 95% CI [1.47-1.66]; p < 0.0001) and culture-positive septic shock (odds ratio, 1.65; 95% CI [1.59-1.71]; p < 0.0001). Conclusions: Patients with culture-negative septic shock behave similarly to those with culture-positive septic shock in nearly all respects; early appropriate antimicrobial therapy appears to improve mortality. Early recognition and eradication of infection is the most obvious effective strategy to improve hospital survival.
Keywords: antimicrobial therapy; infection; mortality; outcome; sepsis; INFLAMMATORY RESPONSE SYNDROME; INTENSIVE-CARE UNITS; SEVERE SEPSIS; DEFINITIONS; INFECTION; MORTALITY